ECO-ENTREPRENEURSHIP DAN PENGUATAN SIKAP PEDULI LINGKUNGAN SISWA DALAM PERSPEKTIF ECOLOGICAL CITIZENSHIP - Ida Purnama Sari; Deni Zein Tarsidi; Joko Daryanto (STKIP Subang, 2026)
In response to the growing environmental problems on a worldwide scale, education plays a crucial role in raising the ecological consciousness of the next generation. The purpose of the article is to examine how, from the standpoint of ecological citizenship, recycling-based eco-entrepreneurship might improve primary children' understanding of the environment. Using a literature review approach, this study looks at pertinent national and international sources about sustainable development, green entrepreneurship, and environmental education. The results show that eco-entrepreneurship initiatives in elementary schools, such waste banks, manufacturing recycled crafts, and using ecobricks, can improve children' ecological consciousness, creativity, and sense of responsibility. The virtues of ecological citizenship, such as compassion, empathy, and practical environmental action, have been shown to be effectively fostered by experiential and collaborative learning methodologies. However, there are still issues with implementation in practice, especially with reference to teachers' lack of knowledge and institutional support. In order to successfully promote eco-entrepreneurship education in primary schools toward the development of sustainable ecological citizens, it is important to increase teacher ability, encourage supporting school policies, and foster community participation.